2012
DOI: 10.1074/jbc.m112.349951
|View full text |Cite
|
Sign up to set email alerts
|

The p63 Protein Isoform ΔNp63α Modulates Y-box Binding Protein 1 in Its Subcellular Distribution and Regulation of Cell Survival and Motility Genes

Abstract: Background: YB-1 is a multifunctional protein that affects transcription, splicing, and translation. Results: ⌬Np63␣, the main p63 protein isoform, interacts with YB-1 and affects YB-1 subcellular localization and regulation of cell survival and motility genes. Conclusion: ⌬Np63␣ and YB-1 interaction inhibits epithelial to mesenchymal transition and tumor cell motility. Significance: This is the first demonstration of a physical and functional interaction between YB-1 and ⌬Np63␣ oncoproteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…In the current study, point mutation of the AKT phosphorylation sites of YB-1(Ser102) did not affect DACH1-mediated nuclear translocation of YB-1 suggesting the mechanism is AKT-independent. The role of other factors showed to regulate YB-1 nuclear translocation, including ΔNP63α (29) remain to be determined. The current studies are the first to define the importance of specific DACH1 phosphorylation sites in regulating function, as DACH1 S439, S441 and S529 were required for nuclear translocation and repression of the Snail 5′UTR Luc reporter.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, point mutation of the AKT phosphorylation sites of YB-1(Ser102) did not affect DACH1-mediated nuclear translocation of YB-1 suggesting the mechanism is AKT-independent. The role of other factors showed to regulate YB-1 nuclear translocation, including ΔNP63α (29) remain to be determined. The current studies are the first to define the importance of specific DACH1 phosphorylation sites in regulating function, as DACH1 S439, S441 and S529 were required for nuclear translocation and repression of the Snail 5′UTR Luc reporter.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in Twist1 expression also correlated with lymph node metastasis in gastric cancer [29] and head and neck carcinoma [30]. Interestingly, ΔNp63, which was the predominant p63 protein isoform in squamous epithelia, reduces the amount of YB-1 bound to the Snail (a potent inducer of EMT) transcript [31]. We previously reported that ΔNp63 was frequently overexpressed in SQ of the lung, and that the ΔNp63 status was useful for distinguishing SQ from adenocarcinoma in adenosquamous carcinoma specimens [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…This decrease in ΔNp63 α is associated with increased migration in SCC cell lines [104]. ΔNp63 α also physically sequesters YB-1, a positive translational mediator of snail, thereby preventing both enhanced snail activity and YB1's function in actin cytoskeleton reorganization, both of which lead to cancer cell migration and invasion [105]. Another direct transcriptional target of ΔNp63 α is the vitamin D receptor (VDR) [106], which is induced by multiple p63 isoforms.…”
Section: P63 and Neoplasiamentioning
confidence: 99%